Pengaruh Profitabilitas, Struktur Modal dan Growth Opportunity Terhadap Nilai Perusahaan - Setianingtiyas, Sinta; Gantino, Rilla (Asosiasi Dosen Akuntansi Indonesia, 2022)
This research aims to analyze the effect of profitability, capital structure, and growth opportunity on company value in food and beverage companies listed on the Indonesia Stock Exchange in 2015-2019. The method used is a saturated sample. The number of sampling used was 19 food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange in 2015-2019. The type of data used is secondary data sourced from financial reports and annual reports. The analytics data method used is multiple linear regression analytics. The hypothesis results test indicates that profitability, capital structure, and opportunity growth simultaneously influence company value. There is a partially positive effect of profitability and capital structure on company value while there is no partial effect of growth opportunity on firm value